New Dromaeosaurids (Dinosauria: Theropoda) from the Lower Cretaceous of Utah, and the Evolution of the Dromaeosaurid Tail - Senter, Phil (Public Library of Science, 2012)
BACKGROUND: The Yellow Cat Member of the Cedar Mountain Formation (Early Cretaceous, Barremian? – Aptian) of Utah has yielded a rich theropod fauna, including the coelurosaur Nedcolbertia justinhofmanni, the therizinosauroid Falcarius utahensis, the troodontid Geminiraptor suarezarum, and the dromaeosaurid Utahraptor ostrommaysorum. Recent excavation has uncovered three new dromaeosaurid specimens. One specimen, which we designate the holotype of the new genus and species Yurgovuchia doellingi, is represented by a partial axial skeleton and a partial left pubis. A second specimen consists of a right pubis and a possibly associated radius. The third specimen consists of a tail skeleton that is unique among known Cedar Mountain dromaeosaurids. METHODOLOGY/PRINCIPAL FINDINGS: Y. doellingi resembles Utahraptor ostrommaysorum in that its caudal prezygapophyses are elongated but not to the degree present in most dromaeosaurids. The specimen represented by the right pubis exhibits a pronounced pubic tubercle, a velociraptorine trait that is absent in Y. doellingi. The specimen represented by the tail skeleton exhibits the extreme elongation of the caudal prezygapophyses that is typical of most dromaeosaurids. Here we perform a phylogenetic analysis to determine the phylogenetic position of Y. doellingi. Using the resulting phylogeny as a framework, we trace changes in character states of the tail across Coelurosauria to elucidate the evolution of the dromaeosaurid tail. CONCLUSIONS/SIGNIFICANCE: The new specimens add to the known diversity of Dromaeosauridae and to the known diversity within the Yellow Cat paleofauna. Phylogenetic analysis places Y. doellingi in a clade with Utahraptor, Achillobator, and Dromaeosaurus. Character state distribution indicates that the presence of intermediate-length caudal prezygapophyses in that clade is not an evolutionarily precursor to extreme prezygapophyseal elongation but represents a secondary shortening of caudal prezygapophyses. It appears to represent part of a trend within Dromaeosauridae that couples an increase in tail flexibility with increasing size.